Lead- free electronics (Wiley-Interscience, 2006)
Lead-free Electronics provides guidance on the design and use of lead-free electronics as well as technical and legislative perspectives. All the complex challenges confronting the elec-tronics industry are skillfully addressed: Complying with state legislation; Implementing the transition to lead-free electronics, including anticipating associated costs and potential supply chain issues; Understanding intellectual property issues in lead-free alloys and their applications, including licensing and infringement; Implementing cost effective manufacturing and testing; Reducing risks due to tin whiskers; Finding lead-free solutions in harsh environments such as in the automotive and telecommunications industries * Understanding the capabilities and limitations of conductive adhesives in lead-free interconnects * Devising solutions for lead-free, flip-chip interconnects in high-performance integrated circuit products